Environmental correlates of body size distribution in Cyprinidae (Actinopterygians) depend on phylogenetic scale. Issue 1 (20th October 2014) - Denys, Gaël P.J.; Tedesco, Pablo A.; Oberdorff, Thierry; Gaubert, Philippe
Abstract: The pattern of increasing species body size with increasing latitude has been noticed in different groups of animals. Here, we used seven key environmental factors and independent contrasts to assess body size latitudinal clines in Cyprinidae at two phylogenetic levels (inter‐ and intragenera), which were defined using a genus‐level supertree. Model selection procedures revealed that environmental factors shaping body size variation in Cyprinidae differed according to the phylogenetic scale considered. At the higher phylogenetic level, we found that both temperature (negative effect) and habitat availability (positive effect of drainage basin surface area) constituted mechanistic explanations of large‐scale body size distribution. No temperature‐related body size cline was observed at the intragenus level. Instead, competitive interaction (negative effect of species richness), habitat availability (positive effect of drainage basin surface area), migration ability and available energy (positive effects of glacial coverage and actual evapotranspiration) constitute alternative explanations at this lower phylogenetic scale. We conclude that (i) at the intergenus level, cyprinids do show a tendency to be smaller at high temperatures and larger at low temperatures, (ii) this tendency no longer exists at the intragenus level, (iii) latitude per se is a weak predictor of body size clines whatever the taxonomic level analysed, (iv) generalising geographical body size patterns may be rendered difficult by the superimposition of a series of mechanisms across different taxonomic scales, and (v) habitat size, here acting positively at both taxonomic scales, may play a major role in shaping riverine species body size clines.